From Stag Party Tourism to Alcohol Cultures - Alix Boirot; Thomas Thurnell-Read (Journal of Festive Studies)
In 2022 Alix Boirot, a social anthropologist with expertise in masculinities, party tourism, and addiction, conducted a lengthy interview with Thomas Thurnell Read, Senior Lecturer at Loughborough University and an internationally recognized scholar specializing in sociological approaches to alcohol, drinking, and drunkenness. Thurnell Read's influential contributions include editing the book Drinking Dilemmas: Space, Culture and Identity (2015) and his founding role in the British Sociological Association's Alcohol Study Group.